2019
DOI: 10.21147/j.issn.1000-9604.2019.03.14
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase II promotes the Warburg effect by phosphorylating alpha subunit of pyruvate dehydrogenase

Abstract: Objective Tumor cells rely heavily on glycolysis regardless of oxygen tension, a phenomenon called the Warburg effect. Hexokinase II (HKII) catalyzes the first irreversible step of glycolysis and is often overexpressed in tumor cells. Mitochondrial HKII couples glycolysis and oxidative phosphorylation while maintaining mitochondrial membrane integrity. In this study, we investigated the role of HKII in promoting the Warburg effect in cancer cells. Methods HKII-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Otto Warburg has verified that tumor cells preferentially uptake glucose as main energy source to produce lactate, even in the present of plentiful oxygen, to support the increased metabolic rate [9], which is well known as "Warburg effect" or "aerobic glycolysis" [10]. The metabolic characteristics is implicated in a series of the alteration of metabolic enzymes, such as glucose transporter 1 (Glut1, also named SLC2A1), hexokinase 2 (HK2), pyruvate kinase type M2 (PKM2) and lactate dehydrogenase A (LDHA) [11][12][13][14][15][16]. Notably, many transcriptional factors including c-myc, hypoxia inducible factor-1α (HIF-1α), nuclear factor kappa-B (NF-κB) promote tumor lactagenesis by regulating the expressions of metabolic enzymes [17][18][19].…”
mentioning
confidence: 99%
“…Otto Warburg has verified that tumor cells preferentially uptake glucose as main energy source to produce lactate, even in the present of plentiful oxygen, to support the increased metabolic rate [9], which is well known as "Warburg effect" or "aerobic glycolysis" [10]. The metabolic characteristics is implicated in a series of the alteration of metabolic enzymes, such as glucose transporter 1 (Glut1, also named SLC2A1), hexokinase 2 (HK2), pyruvate kinase type M2 (PKM2) and lactate dehydrogenase A (LDHA) [11][12][13][14][15][16]. Notably, many transcriptional factors including c-myc, hypoxia inducible factor-1α (HIF-1α), nuclear factor kappa-B (NF-κB) promote tumor lactagenesis by regulating the expressions of metabolic enzymes [17][18][19].…”
mentioning
confidence: 99%
“…An interesting study carried out by Luo F., et al in 2019, reported that not only PDK1 but also Hexokinase II (HKII) that catalyzes the first irreversible step of glycolysis and is often overexpressed in tumor cells, is also able to promote the Warburg effect by phosphorylating alpha subunit of pyruvate dehydrogenase at Serine 293 31 . Therefore we wanted to test if the observed vitamin C-dependent PDK1 inhibition also correlated with a reduction in pyruvate dehydrogenase E1-α phosphorylation at Serine 293.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that 60% of the carbons in glucose are used for fatty acid synthesis, and lipid metabolism also plays vital roles in regulating glucose uptake and glycolytic activities 23 . SREBP-1 is a core transcription factor in lipid metabolism; it induces the transcription of a series of genes involved in fatty acid and triglyceride synthesis 24 .…”
Section: Introductionmentioning
confidence: 99%